Optimising policies to achieve agricultural transformation objectives: An application for Ethiopia - Marco V. Sánchez; Martín Cicowiez (Journal of Applied Economics, 2022)
Policymakers seek objectives that can be conflicting under a budget constraint. Solving this problem requires a multi-criteria decision-making technique whereby equations of a dynamic computable general equilibrium model are constraints to a policy optimisation problem. We illustrate this approach in the framework of agricultural transformation objectives. Using data for Ethiopia we show the potential conflict between policy objectives and how policies are optimally determined to arrive at the best possible compromise. Should Ethiopian policymakers pursue increasing agri-food GDP, rural household welfare, or agri-food exports, for example, they will not necessarily observe strong trade-offs between these objectives. However, if they invest in different agricultural sectors to achieve such objectives, the way in which they finance the investment will result in macroeconomic trade-offs. Only when the new investment is mostly allocated to oilseeds and coffee will there be not only simultaneous but also maximised improvement in all three policy objectives.
Keywords: 330; agricultural transformation; compromise programming; Computable general equilibrium; economic development; optimal policy design